Growth Mindset Can Reduce the Adverse Effect of Substance Use on Adolescent Reasoning - Wang, Cuicui; Luo, Jie; Nie, Peixin; Wang, Daoyang (Frontiers in Psychology, 2019)
The present study examined the relationship between substance use and reasoning in adolescents, and further investigated the modulation role of growth mindset on this relationship. A total of 1759 adolescents in China with substance use experience were investigated. The results showed that substance use (smoking, drinking, and illicit drug use) was negatively correlated with reasoning (r = -0.24 ~-0.39, p< 0.01) and growth mindset (r = -0.18 ~-0.32, p< 0.01). Regression analysis revealed that after controlling for the background variables (i.e. age, family annual income, and parents’ educational level), only illicit drug use was the significant predictor of reasoning (β = -0.325, t = -14.28, p < 0.001). The interaction effect between growth mindset and illicit drug use was also a significant predictor of reasoning (β = -0.067, t = -2.92, p= 0.004), indicating growth mindset modulated the relationship between illicit drug use and reasoning ability. Further analysis found that the negative correlation between frequency of illicit drug use and reasoning in high growth mindset group was weaker than that of low growth mindset group (F(3,1733) = 332.51, p < 0.001, f2 = 0.22). This suggests that growth mindset plays a significant moderating role in the relationship between substance use and reasoning. Overall, substance use has adverse effect on adolescent reasoning, however, growth mindset could reduce this adverse effect.